Nietzsche, postmodernity and truth - Rojas Quispe , Christopher Dante (2021)
The relevance of this work lies in the following: the truth is a concept, especially in the current world, of full validity and, ergo, pertinent. Its objective is to clarify the concept of Nietzsche truth, based on his work “On Truth and Lies in a Nonmoral Sense” and to what extent such clarification strengthens the debate around post-truth. The author’s own ideas were contrasted with the research undertaken by him from a postmodern perspective and those of Gilles Deleuze were used as support. The findings of the reflection proposed by the work are: to consolidate a flexible but nevertheless rigorous approach to truth and post-truth and to strengthen the idea of a Nietzsche whose search was perennial. The main conclusion is: the truth must be constantly localized in a pragmatic conjunction with what the world is now.